Tren Riset Pendidikan Agama Islam pada Google Scholar: Sebuah Analisis Bibliometrik - Wijaya Kusumah, Mada; Kartika Herdiyanti, Meitha; Nur Rahma, Farida (Rayah Al-Islam, 2025)
This research aims to identify prominent themes (research trends) in IRE found on Google Scholar. Employing a bibliometric approach, this study utilizes databases from Google Scholar, spanning the years 2021 to 2024, to examine patterns and developments in IRE research. The research follows a five-step methodology: keyword identification ("Islamic education" OR "Islamic religion education"), article search, article selection, data validation, and data analysis. To analyze the relationships between research themes, authors, journal publishers, and the dissemination of knowledge related to IRE, the Publish or Perish software is employed. Data visualization is performed using VosViewer. The results indicate that trending topics in IRE research include Science, Religion, Islamic Education System; Literature, Culture; Islamic Education Teacher, Knowledge; Islamic Education Management, Philosophy, Life, Islamic Value; World, Country, Covid, Religious Education; Pesantren; and Educational Institutions. The mapping of research themes in this study provides information on research gaps in IRE, which can be utilized by lecturers, researchers, and universities to enhance the quantity and quality of future research.